1993
DOI: 10.5006/1.3316009
|View full text |Cite
|
Sign up to set email alerts
|

Erosion in Disturbed Liquid/Particle Pipe Flow: Effects of Flow Geometry and Particle Surface Roughness

Abstract: Erosion rates were measured along the length of a tubular flow cell of type 304 (UNS S30400) stainless steel (SS) carrying dilute slurries of silica sand (0.43 mm diam) and smooth glass beads of a similar size. The segmented test cell contained a sudden constriction, a sudden expansion, and a groove to produce disturbed flow conditions. Erosion rates were reduced by changes in the cell wall geometry that resulted from erosion at positions of high local metal loss and from erosion further downstream because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…This assumption was considered by many other investigators [9,15,20,21]. This assumption is justiÿed by analysing the experimental results [33] where random erosion downstream of sudden expansion does not exceed 2.5% as compared to impingement erosion. This justiÿes neglecting the in uence of the continuous phase turbulence on particle impact velocity and angle compared to the mean ow in uence.…”
Section: Particle Trackingmentioning
confidence: 98%
See 2 more Smart Citations
“…This assumption was considered by many other investigators [9,15,20,21]. This assumption is justiÿed by analysing the experimental results [33] where random erosion downstream of sudden expansion does not exceed 2.5% as compared to impingement erosion. This justiÿes neglecting the in uence of the continuous phase turbulence on particle impact velocity and angle compared to the mean ow in uence.…”
Section: Particle Trackingmentioning
confidence: 98%
“…To verify the accuracy of the computational scheme, calculations of the erosion rate for pipe contraction were performed and the results were compared with the experimental data of Postlethwaite and Nesic [33]. The pipe sudden contraction simulates the tube sheet in the heat exchanger.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus rounded sand particles, which were apparently smooth, resulted in erosion rates [39] two orders of magnitude greater than the erosion by glass beads in the same system. The difference in behavior was related to the micro-roughness of the sand particles, which could be seen at high magnification under an electron microscope.…”
Section: F2 Solid-particle Impingementmentioning
confidence: 97%
“…It is shown that the in uence of the angle of impact depends greatly on the type of material being brittle or ductile. Prediction of erosion in straight pipes, elbows and tees show the strong in uence of uid properties, sand size and ow velocity on the rate of erosion [30][31][32]. Erosion is deÿned as the wear that occurs when solid particles entrained in a uid stream strike a surface.…”
Section: The Erosion Modelmentioning
confidence: 99%